2022
DOI: 10.1038/s41569-022-00755-0
|View full text |Cite
|
Sign up to set email alerts
|

AIMing 2 treat atherosclerosis

Abstract: The AIM2 inflammasome is activated by host and pathogen DNA. Work from the past 5 years indicates that the AIM2 inflammasome has an important role in advanced atherosclerosis driven by clonal haematopoiesis and possibly in atherosclerosis accelerated by acute infection. Therefore, the AIM2 inflammasome might be an important target for precision medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…47 DNA fragments recognized by AIM2 can be derived from mitochondria, chromosomal DNA and potentially from extracellular sources such as circulating DNA fragments or neutrophil extracellular traps (NETs). 48,49…”
Section: Nlrp3 and Aim2 Inflammasomesmentioning
confidence: 99%
“…47 DNA fragments recognized by AIM2 can be derived from mitochondria, chromosomal DNA and potentially from extracellular sources such as circulating DNA fragments or neutrophil extracellular traps (NETs). 48,49…”
Section: Nlrp3 and Aim2 Inflammasomesmentioning
confidence: 99%
“… 34 , 35 , 36 AIM2 might be an important target for precision medicine of atherosclerosis. 37 Therefore, this study provides a potential pharmacological intervention targeting the AIM2 inflammasome in atherosclerotic cardiovascular disease.…”
Section: Discussionmentioning
confidence: 96%
“…As a novel member of the interferon-induced PYHIN proteins, AIM2 plays a significant role in regulating innate immunity [ 23 ]. Recently, numerous studies, including ours, have shown that AIM2 is associated with pathogenic infections [ 24 , 25 , 26 ]. However, the role of AIM2 in pathogenic C .…”
Section: Discussionmentioning
confidence: 99%